2009
DOI: 10.1021/ef900761t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pressure on the Crystallization of Crude Oil Waxes. II. Evaluation of Crude Oils and Condensate

Abstract: Laboratory analyses of the formation of wax deposits in crude oil are generally performed at atmospheric pressure on stabilized samples without the presence of light components. Therefore, the effects of two important factors that influence the solubility of waxes, namely, light fractions and pressure, are not considered. As a consequence, the results may not reflect what really happens in production lines and equipment. In this work, we evaluated five Brazilian crude oil samples and one condensate, recombined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 17 publications
1
25
1
Order By: Relevance
“…So, the use of calorimetric or microcalorimetric methods to determine enthalpy, entropy or free energy can be insightful to infer the nature and magnitude of forces associated with the phenomenon(a) under investigation. [28][29][30][31][32] Different volumes of asphaltene-in-toluene solutions, resin-in-n-heptane solutions and also pure solvents were mixed in this experimental work. Although, it is indisputable that the changes in the solubility parameter affect the interaction between solutes from different solvents, our aim here was to force the asphaltenes (from the toluene solution) to come out of solution, by adding a bad solvent (resins containing n-heptane), thus generating large specific surface area of asphaltene particles (colloidal ones) with which resins (in n-heptane solution) could promptly interact.…”
Section: Isothermal Microcalorimetrymentioning
confidence: 99%
“…So, the use of calorimetric or microcalorimetric methods to determine enthalpy, entropy or free energy can be insightful to infer the nature and magnitude of forces associated with the phenomenon(a) under investigation. [28][29][30][31][32] Different volumes of asphaltene-in-toluene solutions, resin-in-n-heptane solutions and also pure solvents were mixed in this experimental work. Although, it is indisputable that the changes in the solubility parameter affect the interaction between solutes from different solvents, our aim here was to force the asphaltenes (from the toluene solution) to come out of solution, by adding a bad solvent (resins containing n-heptane), thus generating large specific surface area of asphaltene particles (colloidal ones) with which resins (in n-heptane solution) could promptly interact.…”
Section: Isothermal Microcalorimetrymentioning
confidence: 99%
“…The crystals are thermoplastic in nature and could exist as solid or liquid in solution depending on the temperature and pressure condition of the crude oil (Vieira et al, 2010). The temperature at which all the wax crystals dissolve back into oil (wax dissolution temperature, WDT) is generally higher than the WAT.…”
Section: Wax Deposition and Foulingmentioning
confidence: 99%
“…The paraffin crystallization process can be influenced by many factors such as paraffin composition, solvent nature, polidispersity, rate of cooling, pressure, kinetics and presence of impurities [1,9,14,28,30,[35][36], so that a better knowledge of factors affecting wax solubility will also improve the understanding of the wax precipitation phenomena in the petroleum industry described above. The studies about the effect of solvent on solubility of waxes reported in literature [1] have shown that waxes do not exhibit ideal solution behavior when crystallizing and that their solubility in a solvent increases as both the solvent molecular size and solvent solubility parameter decrease.…”
Section: Experimental Study Of the Influence Of Solvent On Paraffin Cmentioning
confidence: 99%